Interacting quintessence - Zimdahl, Winfried (2001)
We demonstrate that a suitable coupling between a quintessence scalar field and a pressureless cold dark matter (CDM) fluid leads to a constant ratio of the energy densities of both components which is compatible with an accelerated expansion of the Universe.